The Correlation between Inflammatory Cells Density and NF-kB Expression in Fibroinflammatory Nasal Polyps - Suwignyo, Krisnawati Intan; Budiani, Dyah Ratna; Hakim, Fikar Arsyad (Nexus Biomedika, 2016)
Introduction: Asian nasal polyps have more neutrophil-dominant type than Europeanâs (>50%), the difference of histopathology feature may develope because different etiopathogenesis so they need to treat differently. NF-kB is a transcription factor that plays an important role in corticosteroid resistance mechanism in nasal polyps, while corticosteroid is the first choice of medical treatment for nasal polyps. The aim of this research was to determined the correlation between inflammatory cells density and NF-kB expression in fibroinflammatory nasal polyps. Methods: This analytic observational study had cross-sectional design which was done on 15 paraffin embedded fibroinflammatory nasal polyps tissues from patients who had their first nasal polyps surgery and fixed with buffered formalin. The blocks were taken from Anatomical Pathology Department of RSUD Dr. Moewardi and quota sampling was used to collect the samples. Each samples was stainned using hematoxylin-eosin and NF-kB immunohistochemistry technique, both inflammatory cells and NF-kB nuclear positive were counted, then analyzed using Spearman correlation. Result: Coeficient correlation (r) between lymphocytes and nuclear NF-ÎºB in this study was 0.129 (p = 0.647), plasma cells and nuclear NF-ÎºB was 0.404 (p = 0.135), macrophages and nuclear NF-ÎºB was 0.367 (p = 0.178), while neutrophils and nuclear NF-ÎºB was 0.285 (p = 0.301). Conclusions: There is no significant correlation between inflammatory cells density and NF-ÎºB expression in fibroinflammatory nasal polyps. Key Words: nasal polyps, nuclear NF-kB, inflammatory cellsÂ